Clinicopathological significance and prognostic role of LAG3 + tumor-infiltrating lymphocytes in colorectal cancer; relationship with sidedness - Shirin Tavana; Zahra Mokhtari; Mohammad Hossein Sanei; Zahra Heidari; Amir-Reza Dehghanian; Zahra Faghih; Marzieh Rezaei (Cancer Cell International, 2023)
Abstract Background It is well-documented that the interplay between tumor-infiltrating lymphocytes (TILs) and tumor cells is a major determining factor in cancer progression. CD45RO seems to be a reliable indicator for predicting prognosis and disease outcome, along with CD3 and CD8 markers. LAG-3 is another important marker that overexpresses on TILs in a variety of cancers and is associated with disease prognosis; however, its prognostic impact is controversial. Hence, in the present study, we aimed to investigate the presence of CD45RO + , LAG3 + , CD3 + , and CD8 + lymphocytes in CRC tumor tissues and their association with clinicopathological parameters of the disease as well as patients' survival, according to primary tumor locations. Methods Expression of CD45RO, LAG3, CD3, and CD8 was immunohistochemically assessed in tissue sections of 136 patients with CRC. The percentages of TILs expressing these markers were then separately determined in both invasive margin (IM) and center of tumor (CT). Their associations with clinicopathological factors and patients’ survival were analyzed in the entire cohort and the subgroups of patients with right- and left- rectum tumors. Results Based on our observation, CD45RO + and CD3 + cells were the most frequent infiltrated lymphocytes in both CT and IM regions of colon tumor tissue. Whilst, LAG3 + lymphocytes were the least frequent subset in both areas. Statistical analysis indicated that the frequency of CD45RO + TILs was positively associated with advanced TNM stages (III/IV), in the entire cohort and right-sided tumors (P < 0.05). LAG3 + TILs in IM were also increased in tumor tissues with higher T-stages in the entire cohort (P = 0.027). In univariate analysis, high score of CD45RO + TILs in IM was associated with better overall survival in the entire cohort. High score of CD8 + and CD45RO + lymphocytes in IM were also associated with improved survival in patients with right-sided tumors. Conclusions Our findings generally suggest that the clinicopathological and prognostic significance of immune system-related markers such as CD45RO and LAG3 depends on the primary tumor sides. Our results collectively demonstrated that infiltration of CD45RO + lymphocytes in IM could be an independent prognostic factor in a site-dependent manner.